PERSEPSI APARATUR PEMERINTAH TENTANG KUALIFIKASI PROFESI HUMAS - Kokom Komariah; Aat Ruchiat Nugraha; Susie Perbawasari (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
There are still many differences in the views of the public relations profession, namely as a